Evaluating the Therapeutic Impact of L-Carnitine on Postoperative Left Ventricular Ejection Fraction in Patients Undergoing Coronary Artery Bypass Grafting: A Meta-Analysis - Pangkahila, Evangelista Maria; Dewi, Made Yudha Asrithari; Harimawan, Agustinus I Wayan; Silitonga, Josua (Bali Medical and Wellness Journal, 2024)
Background: L-Carnitine (LC) plays a crucial role in transporting long-chain fatty acids into mitochondria for oxidation, which is particularly important for the heart and skeletal muscles. Additionally, it acts as an antioxidant and anti-inflammatory agent, helping to protect tissues from damage caused by reactive oxygen species (ROS). This study aims to evaluate the effect of LC on postoperative left ventricular ejection fraction (LVEF) in patients undergoing coronary artery bypass grafting (CABG). Methods: This systematic review adhered to PRISMA guidelines and searched Google Scholar, PubMed, and ScienceDirect for randomized controlled trials (RCTs) comparing L-Carnitine to placebo in CABG patients. We focused on outcomes related to left ventricular ejection fraction (LVEF) and serum creatine kinase-MB (CK-MB) levels. Data were analyzed using a random-effects model, with results reported as weighted mean differences (WMD) and 95% confidence intervals (CI), considering statistical significance at p < 0.05. Results: The analysis included five RCTs involving 365 CABG patients, with LC doses ranging from 2 to 6 g per day, administered from one month before to 180 days after surgery. The results showed that LC significantly improved LVEF (Weighted Mean Difference [WMD]: 3.22%, 95% Confidence Interval [CI]: 0.28 to 6.16, P = 0.0001). Additionally, LC treatment resulted in a reduction of serum creatine kinase-MB (WMD: -12.75, 95% CI: -22.46 to -3.05, P = 0.01). However, there was no significant difference in cardiopulmonary bypass time between the LC and control groups (WMD: 0.78%, 95% CI: 0.37 to 1.20, P = 0.51). Conclusion: L-Carnitine is effective in improving LVEF and reducing serum CK-MB levels in patients with heart disease undergoing CABG. This suggests it may contribute to a more favorable postoperative recovery.